Recontextualizing dewey’s democracy and education in Indonesia’s pancasila student profile program - Tapung, Marianus (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study investigates the conceptual and practical tensions in implementing democratic education within Indonesia’s Pancasila Student Profile (P5) program by recontextualizing John Dewey’s theory of Democracy and Education. The research addresses the core problem of ideological and institutional misalignment between Dewey’s participatory ideals and the hierarchical, norm-driven structures prevalent in Indonesian schools. Employing a qualitative literature-based approach, the study analyzes 43 selected primary and secondary sources published in the past five years using thematic categorization and interpretative analysis across three dimensions: socio-cultural, pedagogical, and institutional. Findings reveal critical gaps between the democratic ideals of student participation and the top-down school culture; between the goals of democratic education and the applied instructional strategies; and between policy ambitions and fragmented implementation. The study contributes theoretically by adapting Dewey’s progressive educational thought to the collectivist, value-oriented context of Pancasila. Practically, it proposes policy recommendations such as teacher capacity development, institutional reform, and participatory learning environments. The research emphasizes that meaningful democratic education in Indonesia requires not only curriculum innovation but also systemic alignment between educational values, institutional structures, and cultural realities. This recontextualization offers insights for scholars, educators, and policymakers seeking to localize global educational theories within national ideological frameworks.